Complex eigenvalue analysis and dynamic transient analysis in predicting disc brake squeal - Abu Bakar, Abd. Rahim; Ouyang, Huajiang (Publishers Of Distinguished Academic, Scientific And Professional Journals, 2006)
There are typically two different methodologies that can be used to predict squeal in a disc brake, i.e., complex eigenvalue analysis and dynamic transient analysis. The positive real parts of complex eigenvalues indicate the degree of instability of the disc brake and are thought to associate with squeal occurrence or noise intensity. On the other hand, instability in the disc brake can be identified as an initially divergent vibration response using transient analysis. From the literature it appears that the two approaches were performed separately, and their correlation was not much investigated. In addition, there is more than one way of dealing the frictional contact in a disc brake. This paper explores a proper way of conducting both types of analyses and investigates the correlation between them for a large degree-of-freedom disc brake model. A detailed three-dimensional finite element model of a real disc brake is developed. Three different contact regimes are examined in order to assess the best correlation between the two methodologies